Pemberdayaan Hak-Hak Rakyat Atas Tanah - Masyhud Asyhari (Fakultas Hukum Universitas Islam Indonesia, 2000)
The principles of the establishment of the national agrarian law had been formed by the old Order Regime. The law, conceptually, aims to create prosperous society, especially villagers, on the basis of Pancasila (the Five Principle State Ideology), the 1945 Constitution. The real policies of the Old Order Regime to create prosperous society had been issued, however, its implementation had not been optimum. Yet in the New Order Regime, the land rights of societies were often ignored, and even admitted, if these are being facedwith the interest of capital owners. Finally, the society hope, in this reformation era, that their rights on the land can be certainly legalized through the enforcement process of socity rights on land.